Impact of passengers' perceptions of social responsibility activities on the efficacy of PPP urban rail transit projects. (November 2022) - Cui, Caiyun; Han, Xiaowei; Zhou, Qianqian; Xu, Min; Xia, Bo; Skitmore, Martin; Liu, Yong
Abstract: Although public perceptions of social responsibility (SR) activities are considered to provide a useful guide to improving the efficacy of underground infrastructure projects in general to meet the needs of users, little research has been conducted to date in the context of public-private partnership (PPP) urban rail transit (URT) projects. In this paper, a theoretical framework is developed based on the literature review, from which six hypotheses are proposed and tested by structural equation modeling based on data drawn from a questionnaire survey of 708 residents concerning three typical PPP URT projects in Beijing, Dalian, and Hangzhou, China. The results show that, firstly passenger-perceived SR activities have a direct and indirect positive impact on satisfaction, and perceived efficacy, as well as only have a direct influence on perceived quality; secondly passenger-perceived efficacy was influenced by passengers' satisfaction directly and perceived quality indirectly; and thirdly perceived quality has a direct positive influence on satisfaction. The findings contribute to the body of knowledge, provide guidance for project operation management and the sustainable development in the URT domain, by exploring the determinants of the perceived efficacy of PPP URT projects. Highlights: URT passenger-perceived SR activities have positive impact on perceived efficacy. Perceived efficacy was influenced by satisfaction directly and perceived quality indirectly. Perceived quality has a direct positive influence on satisfaction.